The influence of organic ligands on the adsorption of cadmium by suspended matter in natural waters studied by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry and electrochemical methods - Minaberry, Yanina Susana (2010)
Natural water carrying a great amount of suspended particulate matter (SPM) was used as a model system for the study of the competition among organic ligands (dietilentetraamine pentaacetic acid, DTPA, nitrilotriacetic acid, NTA, and citrate, Cit) and natural complexants (SPM) for cadmium adsorption. Speciation diagrams at the pH of the natural sample were obtained by electroanalytical techniques, processing the experimental data with the complexation constants and the mass balance of the system. Results show that the adsorption equilibrium SPM-Cd is completely displaced by DTPA but not completely by NTA or Cit. Furthermore, larger Cit concentrations increase the amount of adsorbed Cd(II). The increment of the complexing capacity may be explained on the basis of SPM-Cit-Cd ternary complexes formation. This hypothesis was supported on the results obtained by applying for the first time the MALDI–TOF technique in a mixture of SPM, Cd(II), organic ligands and their complexes.